1964
DOI: 10.1111/j.1749-6632.1964.tb53130.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Aspects of Fluorine Toxicosis in Cattle*

Abstract: IntroductionFluorine occurs throughout the world in soils, plants, water, and animal tissues.Because of its chemical reactivity, it is found in nature in a combined form.Cattle normally ingest variable amounts of fluorides ( u p to 15 ppm F in dry matter) throughout their lives with no known adverse effects. If amounts above the borderline critical level (which varies with the animal species and the type of fluoride) are ingested over long periods of time, fluorine toxicosis may result. Because fluorine is cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

1967
1967
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 5 publications
0
33
0
2
Order By: Relevance
“…Contudo, o excesso de flúor pode provocar incoordenação motora nos suínos (Bellaver et al, 1991). A sensibilidade à intoxicação por flúor obedece a uma escala decrescente: bovinos, caninos, eqüinos, ovinos, suínos e aves (Shupe & Olson, 1983).…”
Section: Resultsunclassified
“…Contudo, o excesso de flúor pode provocar incoordenação motora nos suínos (Bellaver et al, 1991). A sensibilidade à intoxicação por flúor obedece a uma escala decrescente: bovinos, caninos, eqüinos, ovinos, suínos e aves (Shupe & Olson, 1983).…”
Section: Resultsunclassified
“…A characteristic feature of dental fluorosis is a subsurface hypomineralization of the enamel, which today is widely regarded as being caused by a fluoride-induced disturbance of enamel maturation (Aoba and Fejerskov 2002). The pronounced enamel hypomineralization observed in more severe cases of dental fluorosis causes secondary changes, including pathologically increased dental wear (Fejerskov et al 1983(Fejerskov et al , 1991(Fejerskov et al , 1994Shupe and Olson 1983;Kierdorf and Kierdorf 1989;Kierdorf et al 1993Kierdorf et al , 1996Kierdorf et al , 2000. Studies by Fejerskov (1978, 1979) indicated that the enamel surface defects observed in more severe cases of human dental fluorosis do not represent hypoplasias.…”
Section: Introductionmentioning
confidence: 98%
“…As bone absorbs fluorine, hydroxyls are replaced on the apatite lattice resulting in a weakened structure prompting compensatory growth that can engender lameness-inducing hyperostosis, osteosclerosis, osteomalacia, and osteoporosis (i.e., osteofluorosis) in long-bones (Obel, 1971;Shupe and Olson, 1983). Among large ruminants, metapodials display the highest incidence of osteofluorosis followed by ribs and mandibles (Singh, 1994;Smith, 2001).…”
Section: Fluoride Toxicosismentioning
confidence: 97%